'One R' is the new 'Three Rs'. Issue 5 (November 2014) - Redmond, Craig
The Lush Prize, which rewards initiatives to end animal testing, believes that more attention needs to be given to the 'One R' of absolute replacement, and that research methods that exploit animals in any way (including tissues and cells) should not be considered as 'alternatives'